PELAKSANAAN PROSES BELAJAR MENGAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA SMK PGRI III SALATIGA - - Praptiningsih (Universitas Kristen Satya Wacana, 2015)
Implementation of teaching and learning process of Civic Education at SMK PGRI III Salatiga is a research that related to the use of: Which methods used in the civic education teaching and learning process to determine the sources and means that used in the process of learning and teaching civic education, to know the assessment tools used in teaching and learning process of civic education.The purpose of research is to know the extent of which methods are achieved in the teaching and learning process of Civic Education as desired . Through interviews to Civic Education teachers of SMK PGRI III Salatiga as respondents, obtained data were analyzed qualitatively. Results of the analysis showed that in the implementation of the teaching and learning process of Civic Education, Civic Education teacher taught used vary methods and discussion method in conveying the material. Sources and suggestion which is used in the teaching and learning process is a Civic Education handbook and additional source materials and other means of support. Assessment tool used is a test to measure student progressKey words : Civic Education, Teaching, Learning, metods